2005
DOI: 10.1097/01.nmd.0000180741.93635.ab
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and Posttraumatic Stress Disorder Symptoms Among Low Income Women of Mexican Descent in the United States

Abstract: Survey methods were used to collect cross-sectional data on PTSD symptoms in the context of resources, risks, and strengths of a convenience sample of 315 low income women of Mexican descent. Women were compared by generation in the US, including Mexico-born women who immigrated as adults (> or =age 18), as teens (age 12-17), or as children (< or =age 12), and US-born women whose parents and/or grandparents were Mexico-born. Results showed that US-born women reported significantly more types of trauma than wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 36 publications
2
30
0
1
Order By: Relevance
“…For example, Lown and Vega (2001) found a 10.7 percent prevalence of physical abuse in a socioeconomically diverse population of Mexican-American women, compared to the 54 percent of physical abuse exposure in the present sample. A study focused on similarly impoverished women of Mexican descent seeking primary care at a safety-net clinic in California found comparable rates of physical violence to the present study (Heilemann, Kury et al 2005). It is crucial to identify such intra-ethnic differences because they demonstrate that high rates of interpersonal abuse may stem from contextual factors, such as poverty and immigration stress (see Benson, Wooldredge et al 2004), as opposed to Mexican or Mexican-American ethnicity.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…For example, Lown and Vega (2001) found a 10.7 percent prevalence of physical abuse in a socioeconomically diverse population of Mexican-American women, compared to the 54 percent of physical abuse exposure in the present sample. A study focused on similarly impoverished women of Mexican descent seeking primary care at a safety-net clinic in California found comparable rates of physical violence to the present study (Heilemann, Kury et al 2005). It is crucial to identify such intra-ethnic differences because they demonstrate that high rates of interpersonal abuse may stem from contextual factors, such as poverty and immigration stress (see Benson, Wooldredge et al 2004), as opposed to Mexican or Mexican-American ethnicity.…”
Section: Resultssupporting
confidence: 74%
“…Jennifer Hirsch (2003) found domestic violence similarly to be a problem for married women in Mexico, and argued that the balance of gender and power within Mexican couples was shifting with modernity and migration to the U.S. (Hirsch 2003). Interestingly, evidence in the U.S. suggests that Mexican immigrant populations report higher rates of abuse compared to the general population, and those in Mexico, and that incidence of abuse is higher still among those who are low-income second, third, and fourth generation Mexican-Americans (Holman, Silver et al 2000; Lown and Vega 2001; Heilemann, Kury et al 2005; Baker, Norris et al 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The THQ (Green, 1996), a self-report instrument, was developed to measure history of exposure to potentially traumatic events that may meet the A1 stressor criterion for PTSD. Researchers have employed the THQ in more than 60 non-overlapping published studies (see the reference list for a complete listing), with study populations including, but not limited to, residents of battered women's shelters (Humphreys, Lee, Neylan, & Marmar, 1999), people attending substance abuse clinics (Farley, Golding, Young, Mulligan, & Minkoff, 2004;Najavits, Gastfriend et al, 1998;Najavits, Weiss, & Shaw, 1999), police officers (Brunet et al, 2001;Neylan et al, 2002;Pole, Kulkarni, Bernstein, & Kaufmann, 2006), journalists in Iraq (Feinstein & Nicolson, 2005), Holocaust survivors (Yehuda, Halligan, & Grossman, 2001), adult survivors of childhood trauma and abuse (Hammersley et al, 2003;Heilemann, Kury, & Lee, 2005;Sacks et al, 2008;Spertus, Yehuda, Wong, Halligan, & Seremetis, 2003), and people with life-threatening illnesses (Farley, Golding, & Minkoff, 2002;Green, Krupnick et al, 2000;Spertus, Burns, Glenn, Loftland, & McCracken, 1999).…”
mentioning
confidence: 98%
“…Previous research has revealed that higher acculturation among Hispanics is associated with both PTSD [3234] and alcohol misuse [3541]. Much of this research, however, has involved proxy measures of acculturation (nativity or length of U.S. residence) rather than specific acculturation measures [7,32,42,43].…”
Section: Acculturationmentioning
confidence: 99%